Integrated energy low-carbon economic dispatch considering electricity-carbon price correlation and hydrogen energy storage - HUANG Yuehua; LI Chen; CHEN Chen; YANG Churui; GUO Qianting; LIN Chenjie (Diance yu yibiao)
In order to improve the control of carbon emissions and energy consumption in comprehensive energy under the dual-carbon background, and reduce the proportion of wind curtailment costs, this paper establishes a low-carbon economic dispatch model for comprehensive energy systems that takes into account the electricity-carbon price correlation and hydrogen energy storage. Firstly, considering the fluctuation and interaction between electricity price and carbon price, the Copula function is determined according to the Euclidean distance and the rank correlation coefficient is obtained, and the linear transformation method is used to simulate and sample the relevant electricity and carbon price data. Secondly, hydrogen energy storage is introduced to improve the system energy storage configuration, establish a comprehensive energy optimization scheduling model with the goal of minimizing carbon transaction costs, outsourced energy costs and wind curtailment costs, and CPLEX is used to solve mixed integer linear problems. Finally, the effectiveness of the proposed model is verified by comparative analysis of different scenarios.